OC-019 Optimising The Performance Of Magnetic Assisted Capsule Endoscopy (mace) Of The Upper Gi Tract Using Ct Modelling. (9th June 2014) - Rahman, I; Kay, M; Bryant, T; Pelitari, S; Dimitrov, BD; Patel, P
Abstract : Introduction: Capsule endoscopy, employed to investigate the small bowel, is now being further developed to visualise the upper GI tract. In a pig model, using a hand held magnet, we have demonstrated that magnetic assisted capsule endoscopy (MACE) in the stomach is feasible. However, it is unclear what the best methodology is to achieve complete gastric luminal views in humans. Our aim was to utilise CT modelling of the abdomen to determine the optimal placements of a capsule endoscope in the stomach to allow complete mucosal visualisation and to determine the optimal placement of the hand held magnet to aid pyloric traversing. Methods: Using multiplanar reformatting, 100 good quality contrast abdominal CT scans were analysed to assess luminal visualisation by a magnetic capsule endoscope from 5 fixed stations throughout the stomach. From each station, we assessed the ability of a capsule endoscope to visualise 6 anatomical landmarks (cardia, fundus, body, incisura, antrum and pylorus). Success of visualisation of an anatomical area was only accepted when >90% mucosal visualisation was achieved from a particular station. The pyloric canal angles were calculated to create a vector. We mapped the position of this vector on the patient's skin (pyloric canal vector surface point) to determine the optimal placement of the magnet that would allow traversing of the capsule endoscope through the pylorus. Results: There were 65 female and 35 male patients. Mean age of patients was 53 years (s.d+/-18 years). Best mucosal visualisation of the stomach landmarks was achieved from 3 stations; fundal dependant, antral dependent and opposite the antral dependent points. Maximal visualisation of the whole of the stomach, required combining 2 stations as shown in Table 1 . The box in the figure shows the placement of the magnet in the upper back towards the right loin would allow pyloric traversing of the capsule endoscope in 83% of cases. Increasing age (p = 0.03) and inability to view the pylorus (p = 0.04) were predictors of being outside the box. Conclusion: CT modelling has provided important data regarding the optimal stations in the stomach to position a magnetic capsule endoscope to allow maximal luminal mucosal visualisation and traversing the pylorus. Although there is some extreme variation in the upper GI anatomy, the majority of cases will allow the use of a single standard method in performing MACE which may be very useful for screening purposes. Disclosure of Interest: None Declared.